Track-chart of the U.S. North Pacific Surveying Expedition 1854-1856 / drawn by Louis Waldecker (United States North Pacific Exploring Expedition (1853-1856);, 1856)
Shows tracks of Rodgers, Stevens, Gibson and Brooke. Color; 1:18,000,000